Viktimologi dan Upaya Pemulihan Trauma pada Korban Kejahatan Seksual - Syifatul Zuhra; Muhammad Ryandi Perdana Suandi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Sexual crimes are one of the criminal acts that have serious impacts on the physical, psychological, and social conditions of victims. From a victimology perspective, victims are not only viewed as parties who suffer losses, but also as individuals who require protection, assistance, and comprehensive recovery. This study aims to analyze the role of victimology in understanding the impact of sexual crimes and the trauma recovery efforts that can be provided to victims. The research method used is a qualitative method with a literature study approach through the review of various literature sources, scientific journals, and relevant laws and regulations. The results show that victims of sexual crimes are vulnerable to prolonged trauma such as anxiety disorders, depression, fear, loss of self-confidence, and social disturbances. Trauma recovery efforts can be carried out through psychological assistance, social rehabilitation, family support, counseling, and adequate legal protection. In addition, the role of the government, social institutions, and society is crucial in creating a safe environment and supporting the victim’s recovery process. Therefore, a victimology approach becomes an important foundation in providing protection and recovery oriented toward the rights of victims of sexual crimes.